The changing process towards digital televisión in Perú - Arias Carbajal, Gerardo (2009)
This paper contributes to the reflection on the process of transition from analog television to digital television which is to be broadcasted in Peru and considers that digital television offers a better sound and image quality  and less interference. The process of technological migration may take 1 O years. Peru has already opted for rhe Japanese standard HDTV, which among orher advanrages offers portable and mobile reception. Nonetheless, the high resolution relevision does not seem feasible not does ir make enrreprises more competitive. A question remains to be answered: "If the digital relevision will only serve ro have the same programs at a better resolution, what is the use of having so much invested in time and that the State, the privare entreprises and the public ha ve so much invested in money for such a change?" Besides, the Peruvian television has not yet overcome the poverty inethics and contents that fall to woeful levels during the Fujimori-Montesinos years. On the other hand, Internet competirion has attracted young people as users and producers. That is why it is importanr ro have well-established policies for digital television and to explore new ways of making television